Strategi Gerebek Sampah Pemerintah Kota Depok Menuju Kota Bebas Sampah Tahun 2020 - Indah Wahyu Maesarini; Dodi Rahmat Setiawan; Maya Puspita Dewi (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The waste problem that occurs in almost a number of big cities in Indonesia has a serious impact on these handling efforts. Through the policy launched by the City Government itself, efforts to deal with waste in the city environment itself continue to be carried out and pursued together. Depok City as one of the cities in the West Java region is highly committed to the waste problem that occurs in the Depok City Area.Every day the city of Depok has to deal with 1,250 tons of mounting waste, causing concern for the Depok City Government to immediately handle the waste problem. With the issuance of the Depok City Government Regulation Number 5 of 2015 concerning Waste Management, it has become an important issue of the Depok City Government's work program in the success of the waste management program.The main program carried out by the Depok City Government is through the Strategy Duck Garbage which is expected to be able to solve the waste problem in Depok City. In this study the author uses a qualitative descriptive research method with government informants as competent sources and can answer the strategies carried out by the Depok City Government itself. In addition to Interview with informants, the author also uses Observation and Study of documents to support information